INTEGRATING ENVIRONMENTAL EDUCATION FOR HIGH SCHOOLS IN BALI BASED ON TRI HITA KARANA CONCEPT - Ni Ketut Srie Kusuma Wardhani; Gst. A.A. Riesa Mahendradhani (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
The right to a healthy environment is fundamental for every Indonesian citizen, yet environmental challenges persist. Addressing these issues is not solely the government's responsibility; educational institutions also play a vital role. Schools must nurture future generations with the knowledge, skills, and ethics needed to promote sustainability. The government’s strategy to raise environmental awareness includes integrating environmental education into curricula. This education aims to develop individuals who can actively contribute to environmental protection for both present and future generations. A suitable model for this integration is education based on the values of Tri Hita Karana (THK). THK emphasizes (1) nature preservation, (2) maintaining a healthy school environment, (3) ensuring school cleanliness, and (4) nurturing plant life. By embedding these values into education, schools can enhance students' awareness of environmental protection and empower them to contribute actively to sustainability efforts.